PENGARUH PENGGUNAAN MEDIA FILM KARTUN TERHADAP KETERAMPILAN MENYIMAK CERITA SISWA KELAS V - Sabila, Lala; Marhayani, Dina Anika; Kariadi, Dodik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This experiment aims to determine the effect of using cartoon film media on the listening skills of grade V students. This research was conducted at SD Negeri 27 Singkawang. The type of research used is quantitative experimentation with the Quasi Experimental Design method. The research design used is the posttest only control group design. The population of this study were all fifth grade students of SD Negeri 27 Singkawang with sampling techniques in the form of saturated samples (total sampling). The research was conducted in two classes, namely the experimental class using cartoon film media with 23 students and the control class using textbooks with 23 students. The results of the study can be concluded that: (1) There are differences in the listening skills of fifth grade students using cartoon film media in Indonesian language subjects compared to the listening skills of fifth grade students who use textbooks at SD Negeri 27 Singkawang which are analyzed by t-test with the results of the study > = 3,78 > 2,01; (2) Cartoon film media has a high influence on listening skills in grade V Indonesian language subjects at SD Negeri 27 Singkawang with the calculation of Effect Size of 0.93 (high criteria); (3) There is a positive response to the use of cartoon film media on the listening skills of grade V students, students answer positive statements to get a very good category with an average percentage of 83.28% with a range of 80% < X ≤ 100%.